PERAN BURUH TANI PEREMPUAN TERHADAP EKONOMI KELUARGA DI DESA MEREMBU KECAMATAN LABUAPI KABUPATEN LOMBOK BARAT - Rizka Aulia; Laili Hurriati; Baiq Rizka Milania Ulpah; Ahmad Suhendri (Fakultas Ekonomi dan Bisnis Universitas Islam Al-Azhar Mataram, 2024)
This study entitled “The Role Of Women Farm Laborers In The Family Economy In Merembu Village, Labuapi District, West Lombok Regency’’. The purpose of this study was to determine the role of women farm laborers in the family economy in Merembu Village, Labuapi District, West Lombok Regency. The research method used is descriptive qualitative. This research data was obtained from interviews with female farm laborers in Merembu village. The data collection methods used in this research are observation, interview, and documentation. The results of this study indicate that the role of women farm laborers on the family economy in Merembu village is very large, especially in terms of meeting daily needs such as food, children’s education costs, and other household needs. In addition, they can make a big contribution to the family income, although the income is not too large, it has a very positive impact on the family economy. The contribution of women farm laborers’ income to total family income also varies from 40% to 100%. Women farm laborers who contribute up to 100% to the fulfillment of family needs are those who no longer have a husband or whose husband has died.